L'entrepreneuriat forestier autochtone : le cas de la communauté ilnu de Mashteuiatsh - Beaudoin, Jean-Michel (Université Laval, 2009)
The participation of the First Nations in forestry is a fundamental issue in the province of Québec. For their part, First Nations are considering forestry as a lever to improve the socioeconomic conditions in their communities. Over the last decades, there has been an increasing participation of First Nations in the forestry sector. Unfortunately, little information is currently available on aboriginal community initiatives in regards to business creation. The main objective of this research is to identify key factors that favor or limit aboriginal business creation in forestry. This study first presents the development of forest entrepreneurship within the Ilnu community of Mashteuiatsh, located in the region of Saguenay-Lac-Saint-Jean. The first chapter situates this project in the broader context of Québec forestry. The second chapter draws a portrait of forestry entrepreneurs within this community. The third chapter compares these aboriginal forestry entrepreneurs to non-aboriginal forestry entrepreneurs from the same area. Ours results demonstrate the importance for the aboriginal forest entrepreneur of the social network of the Mashteuiatsh Ilnu community. This network contributes to the differences observed when comparing the portrait, the perceptions and motivations of forestry entrepreneurs within the Ilnu community of Mashteuiatsh to those of non-aboriginal forestry entrepreneurs. In addition, Aboriginal forest entrepreneurs seem more optimist than non-aboriginal entrepreneurs when evaluating they actual situation and future. La participation des communautés autochtones à la foresterie est un enjeu important au Québec. Pour les communautés autochtones, le développement forestier représente des retombées économiques importantes qui peuvent permettre de réduire l’écart entre les conditions socioéconomiques de leur population et celles de la population non-autochtone. Conséquemment, la participation des autochtones à la foresterie a sensiblement augmenté au cours des dernières décennies. Le manque ...